Improving frequency containment reserve provision in run-of-river hydropower plants. (December 2021) - Gerini, F.; Vagnoni, E.; Cherkaoui, R.; Paolone, M.
Abstract: The paper presents a model-based control strategy for optimal asset management of hydroelectric units in run-of-river hydropower plants. The proposed control strategy aims to operate the unit at the best efficiency while improving water flow management and minimise components wear during frequency containment reserve provision. This approach is designed for a double regulated turbine (Kaplan) with adjustable guide vanes angle and runner blades angle and can be extended to other turbines adopted in run-of-river hydropower plants. The optimal discharge set-point is computed for maximising the frequency containment reserve provision while controlling the head of the river. The best efficiency is achieved by solving a suitably defined convex optimisation problem leveraging a regressive model of the hydraulic characteristics of the turbine and dynamics of the guide vanes and blades servomotors. The discharge set-point combines three terms: the dispatch plan set-point, the regulating discharge, proportional to the grid frequency deviation, and an offset term computed to control the average flow through the machine. Furthermore, a method to forecast the energy required in the following hour for the provision of grid frequency regulation is exploited to enhance the unit's frequency containment reserve action. The control strategy is validated by simulating a month of operation for the full-scale run-of-river hydropower plant located in Vogelgrun (France) and by comparing the results with operational statistics. Results show the effectiveness of the proposed control strategy able to increase the provision of frequency containment reserve while decreasing the number of movements of the machine components and maximise the efficiency.